Influence of fluorosubstitution on physical properties of the smectogenic chiral ester. (June 2022) - Deptuch, Aleksandra; Drzewicz, Anna; Dziurka, Magdalena; Górska, Natalia; Hooper, James; Jaworska-Gołąb, Teresa; Juszyńska-Gałązka, Ewa; Marzec, Monika; Piwowarczyk, Marcin; Srebro-Hooper, Monika; Tykarska, Marzena; Urbańska, Magdalena
Highlights: 3F7FPhF and 3F7HPhF with one and two F atoms in aromatic core are compared. Absence of vitrification of smectic C A * phase in doubly-fluorosubstituted 3F7FPhF. Lower tilt angle and longer switching time for 3F7FPhF. Lower frequencies of PL and PH phasons for 3F7FPhF. Slightly higher wavenumbers of two C=O stretching bands for 3F7FPhF. Abstract: Physical properties of the double-fluorinated ( S )-4′-(1-methylheptyloxycarbonyl) biphenyl-4-yl 4-[7-(2, 2, 3, 3, 4, 4, 4-heptafluorobutoxy) heptyl-1-oxy]-2, 3-difluorobenzoate (3F7FPhF) are investigated by several experimental methods (differential scanning calorimetry, polarizing optical microscopy, X-ray diffraction, electro-optic measurements, dielectric and infra-red spectroscopy) complemented with quantum mechanical density functional theory (DFT) and semi-empirical calculations. The phase sequence upon cooling and subsequent heating is reported. Influence of double fluorination of the molecular core on the phase transitions and physical properties is discussed in comparison with the previously reported single-fluorinated glassformer 3F7HPhF. Presence of the second F atom in the molecular core leads to decrease of the layer shrinkage at the smectic A * /smectic C * transition, decrease of the tilt angle and increase of the switching time. It also causes crystallization instead of vitrification of the smectic C A * phase even for high cooling rate (20 °C/min).